2019
DOI: 10.1101/632448
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acylcarnitine Metabolomic Profiles Inform Clinically-Defined Major Depressive Phenotypes

Abstract: Edward Craighead, PhD provided funding to treat non-remitters to the first treatment with combination medication and psychotherapy, to allow follow-up of patients for up to two years to identify predictors of recurrence, and to add patients to the sample to adequately power these studies. Additional support was received from PHS Grant UL1 Abstract Background: Acylcarnitines have important functions in mitochondrial energetics and β oxidation, and have been implicated to play a significant role in metabolic fun… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
(47 reference statements)
2
5
0
Order By: Relevance
“…We may conclude TA B L E 1 Pearson correlation analysis of the top three modules (including acylcarnitines and amino acids) and the blood gene expression data in Alzheimer that CPT1A-dependent regulation of acylcarnitine transfer may control the levels of C12, C14.1, C14.2, and C16 as well as C18 in the plasma during disease progression. Acylcarnitine levels with mitochondrial fatty acid β-oxidation significantly increases in patients with major depression because of the metabolic dysfunction, 49 and the association of medium/long-chain acylcarnitines with AD revealed by this study shows the same notion. Anti-depressants that decrease acylcarnitine levels in major depression patients might be considered a potential treatment for AD patients.…”
Section: Co-expression Metabolite Transcriptome Network Analysis Esta...supporting
confidence: 70%
See 2 more Smart Citations
“…We may conclude TA B L E 1 Pearson correlation analysis of the top three modules (including acylcarnitines and amino acids) and the blood gene expression data in Alzheimer that CPT1A-dependent regulation of acylcarnitine transfer may control the levels of C12, C14.1, C14.2, and C16 as well as C18 in the plasma during disease progression. Acylcarnitine levels with mitochondrial fatty acid β-oxidation significantly increases in patients with major depression because of the metabolic dysfunction, 49 and the association of medium/long-chain acylcarnitines with AD revealed by this study shows the same notion. Anti-depressants that decrease acylcarnitine levels in major depression patients might be considered a potential treatment for AD patients.…”
Section: Co-expression Metabolite Transcriptome Network Analysis Esta...supporting
confidence: 70%
“…Besides the opposite connection between obesity and type 2 diabetes, elevated medium/longchain acylcarnitines in plasma are associated with the disruption of βoxidation in depression. 48,49…”
Section: Consolidated Results and Study Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Acyl-carnitines were increased in both males and females with antidepressant-free rrMDD, and the major vitamins needed for fatty acid oxidation (riboflavin and FAD) were decreased. Disturbances in mitochondrial function leading to acyl-carnitine abnormalities have been observed in several other independent studies of MDD 66 . These findings support the hypothesis that even in remitted rMDD a shift in mitochondrial function exists and persists.…”
Section: The Mitochondrial Nexussupporting
confidence: 55%
“…A recent metabolomics study (13) on >1,000 subjects identified lower levels of the medium-chain acylcarnitines decanoylcarnitine (C10) and dodecanoylcarnitine/laurylcarnitine (C12) in participants with elevated depressive symptoms as compared to controls. Furthermore, ACs profiles have been shown to correlate with depression severity and variation in response to treatment with SSRIs and Ketamine (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%